Green Innovation and Green Accounting on Financial Performance: Literature Review and Future Research Agenda - Lestari, Ni Luh Putu Ratna Wahyu; Wiagustini, Ni Luh Putu; Wirakusuma, Made Gede; Sisdyani, Eka Ardhani (PT. EQUATOR SINAR AKADEMIA, 2025)
This review synthesizes previous literature with the aim of describing and analyzing the state-of-art for evaluating green innovation and green accounting, primarily focusing on financial performance. In addition, it aims to identify institutions and journals that lead publications, theories used, and countries that have researched the most on the influence of green innovation and green accounting on financial performance. Through a systematic literature review (SLR), a search on publish or perish resulted in the receipt of 30 peer-reviewed papers published up to March 2023. Although there was no time limit, the oldest paper was published in 2003, indicating that research on the impact of green innovation and green accounting Financial performance is a topic that is still of great interest today. China, America, as well as the UK and Germany are the countries that publish the most on this theme. In addition, this paper outlines various research gaps on this topic, especially from a methodological point of view. This work has important meaning for industry in formulating policies and strategies to encourage the use of green innovation and green accounting in improving its financial performance. Based on the results, a research agenda for the future has been established.